Oeiras in Late Antiquity: some materials collected in the archaeological excavations carried out at Rua Marquês de Pombal, 3-7 (Historic Center of Oeiras) - Cardoso, João Luís (2018)
The excavations carried out in the Historic Center of Oeiras in 2017/2018 have uncovered structures from different epochs, that reach the Contemporary Age. It goes back to the Roman period the oldest occupation of the site, represented by a building of orthogonal plan, to which succeeded structures later, some of them related to ceramics of Late Antiquity. For their interest, the publication of this small group of pieces was considered justified.